USE OF IMMERSIVE TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATION INSTITUTIONS - Бєлова, Вікторія (SWorldJournal, 2026)
The article highlights the impact of immersive technologies and artificial intelligence on the transformation of education. It analyses the use of virtual, augmented and mixed reality, as well as intelligent digital systems that contribute to the improve